Evaluation Of E-Filling Information System Performance at KPP Pratama Kendari Using COBIT 5.0 Framework - Sriayu Pracita; Fahmi Sahlan (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to evaluate the performance of the E-Filing information system at the Pratama Kendari Tax Office (KPP Pratama Kendari) using the COBIT 5.0 framework approach, and to identify weaknesses, risks, and recommendations for improving system efficiency and reliability. This research employs a qualitative-quantitative analysis approach. Data collection was conducted through in-depth interviews with stakeholders at KPP Pratama Kendari, non-participant observation, Focus Group Discussion (FGD) with experts in taxation and information systems, and surveys of 15 respondents from 2 divisions. Data analysis used the COBIT 5.0 framework, including mapping Enterprise Goals to IT Related Goals and subsequently to COBIT 5.0 Processes, as well as measuring maturity levels using indices 0–5. This research comprehensively applies the COBIT 5.0 Framework in the context of local tax institutions, specifically KPP Pratama Kendari, which has not been extensively explored in previous studies. This research also identifies the readiness of KPP Pratama Kendari in facing the transition from E-Filing to the Coretax DJP system starting in 2026. The research is limited to KPP Pratama Kendari and the 2024 period. Recommendations for improvement are provided in three timeframes: short-term (infrastructure capacity and helpdesk services), medium-term (information security policy development and regular security audits), and long-term (system integration and HR capability enhancement). This research contributes to the development of tax information system policies in the Coretax era.